Thermal management of fuel heat sink in aircraft via flow path optimization - Yang, Shiyu; Lin, Yuanfang; Yu, Haiyu; Xu, Xianghua; Liang, Xingang (Applied thermal engineering, 2024)
•The FHSCR is evaluated and applied to the fuel heat sink optimization.•A new architecture of the AFTMS is designed to enhance the heat dissipation.•The FHSCR is reduced by 14.16% compared to the original architecture.•A dynamic optimal controller based on the MVD-PSO algorithm is established.•Thermal endurance can be extended up to 37.42% and a mission test is conducted. With the rapid increase of aircraft thermal loads, efficiently utilizing the fuel heat sink has received widespread attention in recent years. To improve the performance of the aircraft fuel thermal management system (AFTMS), a concept of the fuel heat sink consumption rate (FHSCR) is proposed to assess the system heat dissipation, and an optimization criterion of fuel heat sink is established based on the FHSCR. Besides, a new architecture of the AFTMS with a middle fuel return branch (MFRB) and a recirculation fuel supply branch (RFSB) is designed to enhance the heat dissipation capacity, and unlike previous studies, only the flow path of the fuel supply and return subsystem (FSRS) has been changed here without additional fuel tanks. Moreover, a dynamic optimal controller based on the particle swarm optimization (PSO) algorithm with the minimum variation distance (MVD-PSO) is developed for obtaining the optimal control parameters and eliminating the parameter oscillation, which is applied in the comparison calculations under both a single condition and a complete mission profile. The calculation results show that compared to the original architecture, the new architecture can reduce the FHSCR by 14.16% under the standard condition, and the thermal endurance of the standard and extreme conditions is extended by 37.42% and 19.54%, respectively. In addition, the new architecture exhibits a better thermal management performance during the whole mission as well. To sum up, comprehensively dealing with the waste heat by both the combustion fuel and ram air is crucial for system cooling, and the new architecture improves the heat dissipation capacity of the AFTMS significantly. This paper provides a novel flow path optimization guide for the AFTMS.